2022
DOI: 10.1039/d2dt00926a
|View full text |Cite
|
Sign up to set email alerts
|

Zero-field slow magnetic relaxation behavior of Zn2Dy in a family of trinuclear near-linear Zn2Ln complexes: synthesis, experimental and theoretical investigations

Abstract: We hereby report a series of near-linear trinuclear [Zn2LnIII(HL)4(CH3COO)].(NO3)2 (where LnIII = La (1-La), Ce (2-Ce), Nd (3-Nd), Sm (4-Sm), Tb (5-Tb), and Dy (6-Dy)) complexes with Schiff base ligand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 79 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…In accordance with the current literature review, it emerges that multidentate Schiff base ligands with distinct coordination environments have been effectively applied in the assembly of polynuclear heterometallic 3d/4f 61–75 and homometallic 4f complexes. 57,76–85 Utilizing the above-mentioned knowledge, we have applied ( E )-2-((pyridin-2-ylmethylene)amino)phenol (LH) in order to construct homometallic lanthanide complexes.…”
Section: Resultssupporting
confidence: 74%
“…In accordance with the current literature review, it emerges that multidentate Schiff base ligands with distinct coordination environments have been effectively applied in the assembly of polynuclear heterometallic 3d/4f 61–75 and homometallic 4f complexes. 57,76–85 Utilizing the above-mentioned knowledge, we have applied ( E )-2-((pyridin-2-ylmethylene)amino)phenol (LH) in order to construct homometallic lanthanide complexes.…”
Section: Resultssupporting
confidence: 74%
“…The thermally activated relaxations above 5 K were best fitted, and values of the parameter related to the Orbach process ( τ 0 =2.13×10 −9 s, U eff / k B =143.44 K (99.8 cm −1 )) and the Raman process ( C =0.23 s −1 K −n , n =3.68) were determined (Figure 5c). From the literature, we know that n is 9 for Kramer ions, but when both the acoustic and optical phonons are considered, depending on the structure of energy levels, n values between 1 and 6 are reasonable [76–87] . To suppress the QTM at low temperatures, a dc field of 2 kOe was applied in the measurements of variable‐frequency χ ′ and χ ′′ for 1 .…”
Section: Resultsmentioning
confidence: 99%
“…From the literature, we know that n is 9 for Kramer ions, but when both the acoustic and optical phonons are considered, depending on the structure of energy levels, n values between 1 and 6 are reasonable. [76][77][78][79][80][81][82][83][84][85][86][87] To suppress the QTM at low temperatures, a dc field of 2 kOe was applied in the measurements of variablefrequency χ' and χ'' for 1. As shown in Figure S7, the near-zero out-of-phase (χ'') signals indicated that the QTM in 1 was effectively quenched.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…[8][9][10][11][12][13] Since the first observation of SMM behavior in a Cu II 2 Tb III 2 coordination compound, 14,15 the construction and characterization of polynuclear 3d-4f coordination clusters have become a very active research area. 16 However, research on 3d-4f SMMs has mainly been focused on Ln-Mn, [17][18][19][20][21] Ln-Co, [22][23][24][25][26][27] Ln-Ni, [28][29][30][31][32] and Ln-Zn 33,34 heterometallic systems and there are relatively few reports on Ln-Fe complexes. Although some Ln III -Fe III heterometallic coordination clusters have been reported, only a few exhibit slow magnetization relaxation in the absence of a static field.…”
Section: Introductionmentioning
confidence: 99%